Digital Product Passport for a Circular Economy - Beck, Sturla; Haggren, Alfred (My University, 2026)
The European Union’s Ecodesign for Sustainable Products Regulation (ESPR) introduces the Digital Product Passport (DPP) as a mandatory requirement to foster a circular economy by ensuring end-to-end traceability and data transparency. While large enterprises are better prepared for this shift, Small and Medium-sized Enterprises (SMEs) which constitute 99% of European enterprises face significant barriers regarding financial resources, technical expertise, and strategic readiness. A review of existing maturity models reveals a critical gap: current frameworks largely assume starting conditions that smaller firms do not possess, leaving SMEs without tailored diagnostic instruments to navigate DPP implementation. To address this gap, this study aims to design, test, and document a DPP readiness assessment tool tailored specifically for SMEs, providing a low-threshold, web-based instrument that outputs a visual maturity profile and a prioritized improvement plan. The study employs a qualitative research design combining inductive and abductive reasoning. Data were collected through semi-structured interviews with 11 subject matter experts across nine companies. Data were analyzed using the Gioia methodology to inductively derive readiness dimensions, which were then mapped against the Socio-Technical Systems Theory (STST) framework. The analysis identified six critical dimensions of DPP readiness: Leadership & Strategy, Human & Organization, Processes & Data Management, Technical Infrastructure, Ecosystem & External Support, and Value Chain & Integration. Among these, Value Chain & Integration emerged as the most critical hurdle, driven by SMEs’ limited purchasing power and the difficulty of enforcing data transparency upstream. Based on these findings, a functional HTML-based self-assessment tool was developed and iteratively refined through pilot testing with six industry practitioners. The results indicate that technical infrastructure alone is insufficient for successful DPP implementation; organizational alignment and strategic ecosystem collaboration are equally vital. Ultimately, the developed readiness tool provides SMEs with an accessible starting point to independently evaluate their baseline preparedness, allowing them to make informed decisions before engaging external service providers.
Keywords: Digital Product Passport (DPP); Circular Economy (CE); Small and Medium-sized Enterprises (SMEs); Readiness assessment; Industry 4.0; Socio-Technical- Systems Theory (STST)